LENSA KONTAK LUNAK DISPOSABLE SEBAGAI ALAT KOREKSI PENGLIHATAN BAGI PENDERITA MIOPIA TINGGI - Wardah; Zakaria Efendi; Murni Marlina Simarmata (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
Multiple soft contact lens options are avaiable for myopia control, from specific myopia control designs to multifocal soft contact lens options. It is important to evaluate the research evidence base for each option. This study was aimed to evaluate the use of disposable-soft contact lense as correction tool to high myopia. This research employed librabry method in gaining data and related informations, then discussed the problem and solution with descriptive approach.